The Interaction of Integrin α(IIb)β(3) with Fibrin Occurs through Multiple Binding Sites in the α(IIb) β-Propeller Domain - Podolnikova, Nataly P. (American Society for Biochemistry and Molecular Biology, 2014)
The currently available antithrombotic agents target the interaction of platelet integrin α(IIb)β(3) (GPIIb-IIIa) with fibrinogen during platelet aggregation. Platelets also bind fibrin formed early during thrombus growth. It was proposed that inhibition of platelet-fibrin interactions may be a necessary and important property of α(IIb)β(3) antagonists; however, the mechanisms by which α(IIb)β(3) binds fibrin are uncertain. We have previously identified the γ370–381 sequence (P3) in the γC domain of fibrinogen as the fibrin-specific binding site for α(IIb)β(3) involved in platelet adhesion and platelet-mediated fibrin clot retraction. In the present study, we have demonstrated that P3 can bind to several discontinuous segments within the α(IIb) β-propeller domain of α(IIb)β(3) enriched with negatively charged and aromatic residues. By screening peptide libraries spanning the sequence of the α(IIb) β-propeller, several sequences were identified as candidate contact sites for P3. Synthetic peptides duplicating these segments inhibited platelet adhesion and clot retraction but not platelet aggregation, supporting the role of these regions in fibrin recognition. Mutant α(IIb)β(3) receptors in which residues identified as critical for P3 binding were substituted for homologous residues in the I-less integrin α(M)β(2) exhibited reduced cell adhesion and clot retraction. These residues are different from those that are involved in the coordination of the fibrinogen γ404–411 sequence and from auxiliary sites implicated in binding of soluble fibrinogen. These results map the binding of fibrin to multiple sites in the α(IIb) β-propeller and further indicate that recognition specificity of α(IIb)β(3) for fibrin differs from that for soluble fibrinogen.